Effects of Trichoderma Biostimulation on the Phenolic Profile of Extra-Virgin Olive Oil and Olive Oil By-Products - Irene Dini; Giulia Graziani; Francesca Luisa Fedele; Andrea Sicari; Francesco Vinale; Luigi Castaldo; Alberto Ritieni (MDPI AG, 2020)
Olive trees are grown on five continents. Fertilization of fields, pest control management, olive leaves, olive pomaces, and olive mill wastewaters have a substantial environmental impact. It is possible to reduce this problem by using organic products to cultivate and decrease olive oil processing waste by recovering the bioactive molecules. In this work, the effects of biostimulation, with beneficial microbes belonging to the Trichoderma genera, and with Trichoderma secondary metabolites (6PP and the HA) were evaluated on the phenolic profile and the antioxidant potential of extra-virgin olive oil (EVOO) and olive leaf samples to make them more commercially attractive as a source of phytochemicals useful for the pharmaceutical, cosmetic, and food industries. Phenolics were identified and quantified by a spectrometer method using Q Exactive Orbitrap UHPLC-MS/MS (Ultra High Pressure Liquid Chromatography). Antioxidant activity was evaluated spectrophotometrically by the DPPH test. The use of Trichoderma strains, 6PP (6-Pentyl-α-Pyrone) and HA (Harzianic Acid), was demonstrated as an effective strategy to increase the leaves' economic value as a source of phytochemicals (flavonoids, lignans, and oleuropein) useful for food, pharmaceutical, and cosmetic industries.